EVALUASI PROGRAM PEMBERDAYAAN EKS PENYANDANG TUNA SOSIAL (GELANDANGAN DAN PENGEMIS) PADA DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU TAHUN 2015 - Adhe Akbar Apiantara; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the framework of the implementation of regional autonomy it is necessary to emphasize on the principles of democracy, community participation, equity and justice in Pekanbaru City. One of the sectors that needs to be achieved is the delivery and translation. Based on these considerations, the city government of Pekanbaru is required to immediately improve the efforts - control efforts and supervision of social welfare. The ineffectiveness of the Social Empowerment Ex-Social Disease Empowerment Program implemented by the Social Service and Funeral of Pekanbaru City, It is seen that the training and development activities in the Social Empowerment Program Ex-Social Disease provided by the social service and the cemetery have not been pressed to sprawl for the job. Analysis in this research is program evaluation theory, theory of coaching and social welfare theory. While the approach used in this study is a qualitative approach with the type descriptive, ie trying to analyze the dynamics and provide explanation of data obtained from observations and objectives reinforce and strengthen a theory to obtain information about the current state. Techniques in collecting data of this research is by using interview technique, documentation and observation. The conclusion of this research evaluation of empowerment of ex-social in Pekanbaru City in handling is done same to homeless and beggars in general but only different in social rehabilitation. Empowerment of ex tuna social done by Social Service and Cemetery Pekanbaru through three effort that is preventive effort, in the form of prevention that still not maximal because there are still many people who have not got socialization of regulation of Pekanbaru City Number 12 Year 2008 about social order. Empowerment of ex tuna social done by Social Service and Cemetery Pekanbaru City through three effort that is preventive effort, repressive and social rehabilitation still not maximal. The inhibiting factor in the effort to empower the ex-social is the budget and infrastructure. The budget provided by the local government is considered not optimal in the effort to run the program already planned so that in the effort of preventive, repressive and social rehabilitation there are still some obstacles caused by the lack of budget and also berkarahun in preparation of adequate facilities and infrastructure。 Keywords: Evaluation, Empowerment, Social Tuna, Social Welfare